Anti-degranulation response of herbal formula in RBL-2H3 cells. (March 2020) - Hu, Jing; Chen, Yujuan; Zhu, Jiajing; Gao, Mingyan; Li, Jiani; Song, Zhengxun; Xu, Hongmei; Wang, Zuobin
Highlights: Anti-degranulation effect of herbal formula studied by biological and physical ways. Herbal formula can inhibit the degranulation of RBL-2H3 cells without cytotoxicity. Morphological and biophysical properties of cells were tailored by herbal formula. Abstract: Allergic diseases not only bring serious economic burden to the patients, but also consume a lot of substantial resources of social medical systems. Thus, the prevention and treatment of allergic diseases are imperative. In this study, the anti-degranulation activity of herbal formula was evaluated using the rat basophil leukemia cells (RBL-2H3) as in vitro model. The morphological and biophysical properties of RBL-2H3 cells before and after treatment with herbal formula were also determined. Notably, the herbal formula exhibits clearly inhibited degranulation by RBL-2H3 cells in a concentration-dependent manner without cytotoxic effect. Therefore, this herbal formula can be used as an alternative and promising therapeutic agent to ameliorate allergic diseases.